2004
DOI: 10.1001/archpsyc.61.9.946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Depression on Infant Nutritional Status and Illness

Abstract: Maternal depression in the prenatal and postnatal periods predicts poorer growth and higher risk of diarrhea in a community sample of infants. As depression can be identified relatively easily, it could be an important marker for a high-risk infant group. Early treatment of prenatal and postnatal depression could benefit not only the mother's mental health but also the infant's physical health and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
483
9
21

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(556 citation statements)
references
References 24 publications
43
483
9
21
Order By: Relevance
“…Indeed, PPD/A in humans have been linked to adverse child outcomes, including later cognitive deficits and emotional disturbances (Feldman et al., 2009; Murray & Cooper, 1996; O'CONNOR, Heron, & Glover, 2002), and PPD specifically has been associated with offspring growth retardation and risk for being underweight (Rahman, Iqbal, Bunn, Lovel, & Harrington, 2004). Similarly, we observed that BCAA mothers had smaller pups at weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PPD/A in humans have been linked to adverse child outcomes, including later cognitive deficits and emotional disturbances (Feldman et al., 2009; Murray & Cooper, 1996; O'CONNOR, Heron, & Glover, 2002), and PPD specifically has been associated with offspring growth retardation and risk for being underweight (Rahman, Iqbal, Bunn, Lovel, & Harrington, 2004). Similarly, we observed that BCAA mothers had smaller pups at weaning.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (61.7%) of studies were facility-based, 34.0% were community-based and n=2 studies were conducted in both settings. The range of study designs is wide, from small-n (n=18) qualitative research (Niemi et al, 2010) to case control design (n=320) Rahman et al, 2004a) to large-scale (n=19,030) experimental intervention research (Tripathy et al, 2010). …”
Section: Figure 1 About Herementioning
confidence: 99%
“…Health Maternal health/nutrition/hunger (Bell et al, 2008;Nakku et al, 2006;Pollock et al, 2009) (Ho-Yen et al, 2007Nakku et al, 2006;Patel et al, 2002;Pollock et al, 2009) - Infant health (Patel et al, 2002;Rahman et al, 2004b) Rahman et al, 2004a;Ross et al, 2010) (Adewuya et al, 2008;Patel et al, 2002;Rahman et al, 2004b) ---…”
Section: Table 2: Examples Of Poverty Indicator Definitions From Studmentioning
confidence: 99%
“…3 Although only 5 to 8% of pregnant women meet criteria for major depressive disorder, 4 about 20% of women may experience depressive symptoms during pregnancy and postpartum and this situation often goes undiagnosed and untreated. [4][5][6] This is an important risk factor for postnatal depression and evidence suggests that gestational depression may be associated with several negative outcomes, such as low birth weight, preterm birth, and abnormal child development. [5][6][7][8] Conventional treatment options for depression include psychotropic agents (especially antidepressants), psychotherapy, and electroconvulsive therapy (ECT), which is indicated in the most severe or treatmentrefractory cases.…”
Section: Introductionmentioning
confidence: 99%